Qardh Contract in the Peccoten Tradition (Analytic Study of the Peccoten Tradition in the Madura Kubu Raya Circle) - Miskari, Miskari (JURNAL ISLAM NUSANTARA, 2022)
This study aims to determine the contract contained in the Peccoten tradition, which uses cigarettes, soap, cloth and others as tools to invite marriage. The Peccotan tradition, which is a Madurese tradition, is still carried out by those who live in Madusari Village, Sungai Raya District, Kubu Raya Regency. The object of this research is the symbolic meaning of cigarettes used as a medium for invitations to pickpockets found in Samatan Village. The collection technique in this study uses a descriptive qualitative research method to reveal the implied meaning of the symbolization of cigarettes in the peccotan tradition. This research data collection includes observation, documentation and direct interviews in Madusari Village. Collecting data from resource persons such as Madurese leaders and Islamic religious leaders who have long practised the Peccotan tradition in Madusari village. There were six resource persons used in this study consisting of people who had used the pecotan tradition and received an invitation to pecotan in Samatan Village. The results showed that in the pecotan tradition in Samatan Village, there was a symbolic interaction where cigarettes which were used as invitation media had different types of cigarettes used as invitation media; the difference was in the type of cigarettes and the number of envelopes given and the pecotan tradition has become a hereditary tradition that continues until today in Madusari Village, Kub Raya Regency.